BIRDIE: A data pipeline to inform wetland and waterbird conservation at multiple scales - Cervantes, Francisco; Altwegg, Res; Strobbe, Francis; Skowno, Andrew; Visser, Vernon; Brooks, Michael; Stojanov, Yvan; Harebottle, Douglas M.; Job, Nancy (Frontiers in Ecology and Evolution, 2023)
With increasing pressure on ecosystems, we have seen substantial efforts in the collection and management of ecological data, over the last decade. This is especially true for freshwater ecosystems, which are among the most impacted by human activity and yet they have been lagging behind in terms of data availability, compared to other terrestrial ecosystems. Despite improvements in data collection and accessibility, raw data still need to be analysed and interrogated to support conservation programmes and management decisions, a process that can be complex and time consuming. The South African Biodiversity Data Pipeline for Wetlands and Waterbirds (BIRDIE) aims to help fast and efficient information uptake, bridging the gap between raw ecological datasets and final users. BIRDIE is a full data pipeline that takes up raw data, and through a series of processing steps, estimates indicators related to abundance, distribution and diversity of waterbirds, keeping track of their associated uncertainty. It focuses on the assessment of waterbird populations in South Africa and uses two citizen-science bird monitoring datasets, namely: the African Bird Atlas Project and the Coordinated Waterbird Counts. In addition, a suite of environmental layers help contextualise waterbird population indicators, and link these to the ecological condition of the supporting wetlands. Data processing is conveniently organised in modules that can be run independently, and include tasks, such as: occupancy modelling, state-space modelling, and computation of indicators at multiple temporal and spatial scales. Both data and indicators are accessible to end users through an online portal and through web services. Envisioned users of BIRDIE include government officials, conservation managers, researchers and the general public. Acknowledging that conservation programmes run at multiple scales, from site management to international agreements, we have developed a granular framework in which waterbird population indicators are estimated at small scales, and then these are aggregated to compute similar indicators at broader scales. The online portal is designed to provide spatial and temporal visualisation of the indicators using maps and time series, to help contextualization. This paper describes the structure of the BIRDIE pipeline and the technical features underpinning its components.